Diversidade e filogenia molecular de rizóbios associados a Desmodium spp. - nativos dos Campos Gerais do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Considering the great richness and abundance of leguminous plants in the Campos Gerais region, as well as the existing gaps regarding microbial biodiversity in the region, the present study carried out, through an exploratory survey, the isolation of twenty-nine rhizobia of root nodules of host plants of the species Desmodium barbatum, D. incanum and D. discolor. The specimens come from three conservation areas of Campos Gerais: Campos Gerais National Park, Vila Velha State Park (both in Ponta Grossa-PR), and Cerrado State Park (Jaguariaíva-PR). The soils of the study areas were characterized as acids and presented great variation between the macronutrient values, presenting low natural fertility. Phylogenetic analysis based on the 16S rDNA and recA genes allowed the classification of eighteen strains as Alfaproteobacteria, one belonging to the genus Allorhizobium, four to the genus Rhizobium and thirteen strains belonging to the genus Bradyrhizobium. Eleven strains of Betaproteobacteria classified as Paraburkholderia spp were isolated, whose taxonomic inferences based on the phylogeny of the 16S DNAr gene were related to their respective geographical origins. By means of the BOX-PCR technique, there was a high genomic variability between the strains, since all the isolates presented unique profiles. In this context, the analysis of the diversity of rhizobia associated with Desmodium spp. allowed the confirmation of its symbiotic promiscuity, especially of the species D. barbatum. In addition, the isolation of beta-rhizobia belonging to the genus Paraburkhold
Keywords: fixação biológica de nitrogênio; simbiose; leguminosas; unidades de conservação.; biological fixation; microsymbiont; leguminous; conservation unit; CNPQ::CIENCIAS BIOLOGICAS